Adaptation and characterization of thermophilic anammox in bioreactors. (1st April 2020) - Vandekerckhove, Tom G.L.; Props, Ruben; Carvajal-Arroyo, José M.; Boon, Nico; Vlaeminck, Siegfried E.
Abstract: Anammox, the oxidation of ammonium with nitrite, is a key microbial process in the nitrogen cycle. Under mesophilic conditions (below 40 °C), it is widely implemented to remove nitrogen from wastewaters lacking organic carbon. Despite evidence of the presence of anammox bacteria in high-temperature environments, reports on the cultivation of thermophilic anammox bacteria are limited to a short-term experiment of 2 weeks. This study showcases the adaptation of a mesophilic inoculum to thermophilic conditions, and its characterization. First, an attached growth technology was chosen to obtain the process. In an anoxic fixed-bed biofilm bioreactor (FBBR), a slow linear temperature increase from 38 to over 48 °C (0.05–0.07 °C d −1 ) was imposed to the community over 220 days, after which the reactor was operated at 48 °C for over 200 days. Maximum total nitrogen removal rates reached up to 0.62 g N L −1 d −1 . Given this promising performance, a suspended growth system was tested. The obtained enrichment culture served as inoculum for membrane bioreactors (MBR) operated at 50 °C, reaching a maximum total nitrogen removal rate of 1.7 g N L −1 d −1 after 35 days. The biomass in the MBR had a maximum specific anammox activity of 1.1 ± 0.1 g NH4 + -N g −1 VSS d −1, and the growth rate was estimated at 0.075–0.19 d −1 . The thermophilic cultures displayed nitrogen stoichiometry ratios typical for mesophilic anammox: 0.93–1.42 g NO2 - -Nremoved g −1 NH4 + -Nremoved and 0.16–0.35 g NO3 - -Nproduced g −1 NH4 + -Nremoved . Amplicon and Sanger sequencing of the 16S rRNA genes revealed a disappearance of the original "Ca. Brocadia" and "Ca. Jettenia" taxa, yielding Planctomycetes members with only 94–95% similarity to "Ca. Brocadia anammoxidans" and "Ca. B. caroliniensis", accounting for 45% of the bacterial FBBR community. The long-term operation of thermophilic anammox reactors and snapshot views on the nitrogen stoichiometry, kinetics and microbial community open up the development path of thermophilic partial nitritation/anammox. A first economic assessment highlighted that treatment of sludge reject water from thermophilic anaerobic digestion of sewage sludge may become attractive. Graphical abstract: Image 1 Highlights: A slow temperature increase on a mesophilic inoculum enabled thermophilic anammox. A potentially novel species was highly abundant in the adapted community. Stoichiometry and rescaled kinetics are low compared to mesophilic anammox cultures. An attached and a suspended growth reactor were feasible. Thermophilic partial nitritation/anammox may become economically cost-effective.